2012
DOI: 10.1504/ijnt.2012.046748
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Pt<SUP align="right">n+</SUP>–CeO<SUB align="right">x catalyst films grown on carbon substrates

Abstract: Deposition of the Pt doped cerium oxide catalyst layers on carbon nanotubes and flat carbon substrates by magnetron sputtering leads to growth of solid solution films composed of nanorods oriented perpendicularly to the substrate surface forming fractal like highly porous structure. The films contain only cationic Pt 2+ and Pt 4+ . Cerium oxide is partially reduced. The catalyst films reveal high catalytic activity as anode catalyst in proton exchange membrane fuel cells. Preparation of nanoporous structures b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The prepared layers have exhibited a complex porous columnar structure with an increased active surface of the catalyst compared to a relatively flat layer deposited on a silicon substrate. 25,26,28,[36][37][38][39] In very recent reports, 40,41 we have shown that the morphology of the nanostructured ceria layers can be tuned by different preparation conditions, mainly by the working gas composition, r.f. discharge power and deposition time.…”
Section: Introductionmentioning
confidence: 99%
“…The prepared layers have exhibited a complex porous columnar structure with an increased active surface of the catalyst compared to a relatively flat layer deposited on a silicon substrate. 25,26,28,[36][37][38][39] In very recent reports, 40,41 we have shown that the morphology of the nanostructured ceria layers can be tuned by different preparation conditions, mainly by the working gas composition, r.f. discharge power and deposition time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that highly porous coatings can be prepared by magnetron sputtering implying a high application potential in catalysis. [23] Most interestingly, dispersed Pt-CeO 2 composites with any Pt:Ce ratio can be prepared by cosputtering, in direct analogy to the model catalysts discussed above. We have also demonstrated the promising properties of the Pt-CeO 2 coating as electrocatalysts in proton exchange membrane fuel-cell technology, specifically their superior noble metal efficiency.…”
mentioning
confidence: 99%
“…We have also demonstrated the promising properties of the Pt-CeO 2 coating as electrocatalysts in proton exchange membrane fuel-cell technology, specifically their superior noble metal efficiency. [22,23] Recently we compared Pt-CeO 2 anodes with different Pt loadings between 0 and 10 mg Pt/cm 2 (see Supporting Information) The highest performance was shown for the catalyst with 2 mg Pt/cm 2 which contained Pt 2+ ions only. For higher loading, Pt was in both the Pt 2+ and the Pt 0 state and the performance of the catalyst was lower (Supporting Information, Figure S5).…”
mentioning
confidence: 99%